Mitochondrial DNA Hypomethylation Is a Biomarker Associated with Induced Senescence in Human Fetal Heart Mesenchymal Stem Cells - Dehai Yu; Zhonghua Du; Lingling Pian; Tao Li; Xue Wen; Wei Li; Su-Jeong Kim; Jialin Xiao; Pinchas Cohen; Jiuwei Cui; Andrew R. Hoffman; Ji-Fan Hu (Stem Cells International)
Background. Fetal heart can regenerate to restore its normal anatomy and function in response to injury, but this regenerative capacity is lost within the first week of postnatal life. Although the specific molecular mechanisms remain to be defined, it is presumed that aging of cardiac stem or progenitor cells may contribute to the loss of regenerative potential. Methods. To study this aging-related dysfunction, we cultured mesenchymal stem cells (MSCs) from human fetal heart tissues. Senescence was induced by exposing cells to chronic oxidative stress/low serum. Mitochondrial DNA methylation was examined during the period of senescence. Results. Senescent MSCs exhibited flattened and enlarged morphology and were positive for the senescence-associated beta-galactosidase (SA-β-Gal). By scanning the entire mitochondrial genome, we found that four CpG islands were hypomethylated in close association with senescence in MSCs. The mitochondrial COX1 gene, which encodes the main subunit of the cytochrome c oxidase complex and contains the differentially methylated CpG island 4, was upregulated in MSCs in parallel with the onset of senescence. Knockdown of DNA methyltransferases (DNMT1, DNMT3a, and DNMT3B) also upregulated COX1 expression and induced cellular senescence in MSCs. Conclusions. This study demonstrates that mitochondrial CpG hypomethylation may serve as a critical biomarker associated with cellular senescence induced by chronic oxidative stress.